1995
DOI: 10.1021/bc00035a009
|View full text |Cite
|
Sign up to set email alerts
|

Synthesis and Use of a Biotinylated 3-Azidophenothiazine to Photolabel Both Amino- and Carboxyl-Terminal Sites in Calmodulin

Abstract: The biotinylated probe, 3-azido-10-(4-(4-biotinyl-1-piperazinyl)butyl)phenothiazine, was used to examine the phenothiazine binding domains in calmodulin (CaM) by photolabeling. This phenothiazine, synthesized from 3-azido-10-(4-(1-piperazinyl)butyl)phenothiazine and d-biotinyl tosylate, inhibited the CaM-mediated activation of phosphodiesterase (PDE) with an I50 of 12.5 (+/- 2.8) microM. Photolabeling of CaM produced covalent adducts in excellent yield (32%) in a light- and Ca2+-dependent manner. Studies perfo… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

2
11
0

Year Published

1995
1995
2017
2017

Publication Types

Select...
7
1

Relationship

1
7

Authors

Journals

citations
Cited by 11 publications
(13 citation statements)
references
References 39 publications
2
11
0
Order By: Relevance
“…Attempted tosylation in anhydrous pyridine resulted in a mixture of the tosylate 11a (19 %) and chloride 11b (16%) (35 % combined yield). This appearance of the chloro species 11b in the reaction of biotinol with sulfonyl chlorides has been previously observed by Islam et al 28 In this report the treatment of biotinol with methanesulfonyl chloride gave both the mesylate and chloride. Use of excess pyridine in the tosylation reaction, in our case by its use as solvent, can facilitate formation of chloro species by reaction of the pyridinium chloride by-product with the newly formed tosylate.…”
Section: Raft Polymerizationsupporting
confidence: 86%
See 1 more Smart Citation
“…Attempted tosylation in anhydrous pyridine resulted in a mixture of the tosylate 11a (19 %) and chloride 11b (16%) (35 % combined yield). This appearance of the chloro species 11b in the reaction of biotinol with sulfonyl chlorides has been previously observed by Islam et al 28 In this report the treatment of biotinol with methanesulfonyl chloride gave both the mesylate and chloride. Use of excess pyridine in the tosylation reaction, in our case by its use as solvent, can facilitate formation of chloro species by reaction of the pyridinium chloride by-product with the newly formed tosylate.…”
Section: Raft Polymerizationsupporting
confidence: 86%
“…These data were found to have some discrepancy compared with those reported in literature. 27,28 It is suggested that some of the NMR data may have been misreported as the product reported in literature was not purified after the Soxhlet extraction.…”
Section: Synthesis Of 4s-[(3as6ar)-5-hydroxy-pentyl]-tetrahydrothienmentioning
confidence: 99%
“…4S-[(3aS,6aR)-5-Iodopentyl]tetrahydro- 1 H - thieno[3,4-d]imidazol-2(3H)-one ( 3 ) [ 15 ]. This compound was prepared from biotin tosylate as reported [ 22 ]. The biotin tosylate (280 mg, 0.75 mmol) and NaI (216 mg, 0.15 mmol) were stirred in acetone (20 mL) for 24 h. The solvent was removed under reduced pressure and the residue was dissolved in CH 2 Cl 2 and the organic layer was successively washed with sodium thiosulfate (1.0 N) and water, dried over anhydrous Na 2 SO 4 , and concentrated under vacuum.…”
Section: Methodsmentioning
confidence: 99%
“…Gel-filtration experiments indicated that chlorpromazine, which is structurally similar to TFP, binds at not four but five binding sites [19]. Photolabelling of CaM with a reactive phenothiazine derivative indicated two binding sites, one in each globular domain [20]. "H-, %$Caand ""$Cd-NMR studies indicated the presence of two distinct binding sites for TFP in which the affinities differ by one or two orders of magnitude [21][22][23].…”
Section: Figure 1 Chemical Structures Of W-7 (Left) and Tfp (Right)mentioning
confidence: 99%